Kajian Literatur: Suplementasi Vitamin D Mengurangi Tingkat Keparahan serta Mencegah dan Mengobati COVID-19 - Istiqomah, Ayuningtyas; Utami, Wahyu (Jurnal Farmasi Udayana; Vol. 12, No 1, Tahun 2023, 2023)
Supplementation can play a supporting role in COVID-19 patients, one of which is the provision of vitamin D supplementation. This study aims to discuss and examine the existing evidence regarding the effect of vitamin D supplementation in reducing severity and preventing/treating COVID-19. The method used is a literature study from various library sources that can be accessed using the PubMed and Google Scholar databases with the keywords [(“Vitamin D” OR “Vitamin D2” OR “Vitamin D3”) AND (“COVID-19” OR “Coronavirus Disease 2019” OR “SARS CoV 2”)]. Sixty-eight studies met the inclusion and exclusion criteria and are therefore included in this literature review. This study shows that the lower the level of vitamin D in the body, the higher the severity of COVID-19. In addition, the use of vitamin D supplementation has a positive effect on COVID-19 by reducing the risk of being infected with COVID-19, reducing the risk of death, and reducing the severity of COVID-19. This could be because vitamin D can enhance the innate immune system which is the body's first line of defense against pathogens and regulate the adaptive immune system to reduce cytokine storms, and has a potential protective role against acute respiratory distress syndrome by inhibiting the renin-angiotensin pathway. Therefore, vitamin D supplementation can be used as an additional treatment for COVID-19.